Superiority of [(68)Ga]-DOTATATE PET/CT to other functional imaging modalities in the localization of SDHB-associated metastatic pheochromocytoma and paraganglioma - Janssen, Ingo (Clin Cancer Res, 2015)
PURPOSE: Patients with succinate dehydrogenase subunit B (SDHB) mutation-related pheochromocytoma/paraganglioma (PHEO/PGL) are at a higher risk for metastatic disease than other hereditary PHEOs/PGLs. Current therapeutic approaches are limited but the best outcomes are based on the early and proper detection of as many lesions as possible. Because PHEOs/PGLs overexpress somatostatin receptor 2 (SSTR2), the goal of our study was to assess the clinical utility of [(68)Ga]-DOTA(0)-Tyr(3)-octreotate ([(68)Ga]-DOTATATE) positron emission tomography/computed tomography (PET/CT) and to evaluate its diagnostic utility in comparison to the currently recommended functional imaging modalities [(18)F]-fluorodopamine ([(18)F]-FDA), [(18)F]-fluorodihydroxyphenylalanine ([(18)F]-FDOPA), [(18)F]-fluoro-2-deoxy-D-glucose ([(18)F]-FDG) PET/CT as well as CT/magnetic resonance imaging (MRI). EXPERIMENTAL DESIGN: [(68)Ga]-DOTATATE PET/CT was prospectively performed in 17 patients with SDHB-related metastatic PHEOs/PGLs. All patients also underwent [(18)F]-FDG PET/CT and CT/MRI with 16 of the 17 patients also receiving [(18)F]-FDOPA and [(18)F]-FDA PET/CT scans. Detection rates of metastatic lesions were compared between all these functional imaging studies. A composite synthesis of all used functional and anatomical imaging studies served as the imaging comparator. RESULTS: [(68)Ga]-DOTATATE PET/CT demonstrated a lesion-based detection rate of 98.6% (95% confidence interval (CI) 96.5% to 99.5%), [(18)F]-FDG, [(18)F]-FDOPA, [(18)F]-FDA PET/CT, and CT/MRI showed detection rates of 85.8% (CI 81.3% to 89.4%) (p<0.01), 61.4% (CI 55.6% to 66.9%) (p<0.01), 51.9% (CI 46.1% to 57.7%) (p<0.01), and 84.8% (CI 80.0% to 88.5%) (p<0.01), respectively. CONCLUSIONS: [(68)Ga]-DOTATATE PET/CT showed a significantly superior detection rate compared to all other functional and anatomical imaging modalities and may represent the preferred future imaging modality in the evaluation of SDHB-related metastatic PHEO/PGL.